Operations management in the hospitality industry - Szende, Peter; Dalton, Alec N.; Yoo, Michelle (Emerald Publishing Limited, 2021)
From restaurants to resorts, the hospitality industry demands strong operations management to delight guests, develop employees, and deliver financial returns. This introductory textbook provides students with fundamental techniques and tools to analyse and improve operational capabilities of any hospitality organization.- Resumé vydavatel
Keywords: pohostinství; management cestovního ruchu; catering trade; tourism management; elektronické knihy; učebnice vysokých škol; electronic books; textbooks (higher)